Zooming in on Cryopreservation of hiPSCs and Neural Derivatives: A Dual-Center Study Using Adherent Vitrification - Kaindl, Johanna; Meiser, Ina; Majer, Julia; Sommer, Annika; Krach, Florian; Katsen-Globa, Alisa; Winkler, Jürgen; Zimmermann, Heiko; Neubauer, Julia C.; Winner, Beate (Stem Cells Translational Medicine, 2019)
Human induced pluripotent stem cells (hiPSCs) are an important tool for research and regenerative medicine, but their efficient cryopreservation remains a major challenge. The current gold standard is slow-rate freezing of dissociated colonies in suspension, but low recovery rates limit immediate post-thawing applicability. We tested whether ultrafast cooling by adherent vitrification improves post-thawing survival in a selection of hiPSCs and small molecule neural precursor cells (smNPCs) from Parkinson's disease and controls. In a dual-center study, we compared the results by immunocytochemistry (ICC), fluorescence-activated cell sorting analysis, and RNA-sequencing (RNA-seq). Adherent vitrification was achieved in the so-called TWIST substrate, a device combining cultivation, vitrification, storage, and post-thawing cultivation. Adherent vitrification resulted in preserved confluency and significantly higher cell numbers, and viability at day 1 after thawing, while results were not significantly different at day 4 after thawing. RNA-seq and ICC of hiPSCs revealed no change in gene expression and pluripotency markers, indicating that physical damage of slow-rate freezing disrupts cellular membranes. Scanning electron microscopy showed preserved colony integrity by adherent vitrification. Experiments using smNPCs demonstrated that adherent vitrification is also applicable to neural derivatives of hiPSCs. Our data suggest that, compared to the state-of-the-art slow-rate freezing in suspension, adherent vitrification is an improved cryopreservation technique for hiPSCs and derivatives. Stem Cells Translational Medicine 2019;8:247&259.
EVALuna2:36383